INOVASI KONSEP PEMBELAJARAN BLENDED LEARNING PADA SAAT PANDEMI COVID-19 UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Vieto Budi Utomo; Slamet Widodo (LPPM Universitas Bina Bangsa, 2023)
Covid-19 has spread to every country in the world, including Indonesia. Many areas of Indonesian life have experienced obstacles since the entry of the Corona virus, also known as Covid-19, in this country, especially the education system. In Indonesia, a developing country, the pandemic continues to be a challenge for the country's education system. This is the main reason why many places in Indonesia are experiencing economic, educational or technical problems. The various zones are now depicted by government signage using colors and symbols to distinguish them from one another. These locations include the red zone, orange zone, yellow zone, and green zone. Students are still using distance learning (PJJ) in an effort to stop the spread of Covid-19, as indicated by the red and orange zones. The yellow and green zones indicate that students are allowed to do face-to-face learning in schools, but are not required. The purpose of this article is to explain how to use a blended learning approach during a pandemic to increase student interest in learning. Blended learning is learning that combines various types of learning methods. Online, offline, and self-study approaches are all included in blended learning. Some places, such as the yellow zone and the green zone, find it difficult to get a decent signal. This strategy can also be used in economically troubled areas. During the Covid-19 pandemic, this study sought to determine whether or not the blended learning approach was successful in increasing student interest in learning. This study uses a qualitative descriptive technique based on a literature study or literature review